Training guide administrating Windows Server 2012 R2 - Thomas, Orin 1973- (Microsoft Press, 2014)
Fully updated for Windows Server 2012 R2! Designed to help enterprise administrators develop real-world, job-role-specific skills - this Training Guide focuses on core infrastructure administration for Windows Server 2012 R2. Build hands-on expertise through a series of lessons, exercises, and suggested practices - and help maximize your performance on the job. This Microsoft Training Guide : Focuses on job-role-specific expertise for core infrastructure administration tasks Fully updated for Windows Server 2012 R2, including new practices Provides in-depth, hands-on training you take at your own pace Creates a foundation of skills which, along with on-the-job experience, can be measured by Microsoft Certification exams such as 70-411 Topics include: Deploying and updating Windows Server 2012 R2 Managing account policies and service accounts Configuring name resolution Administering Active Directory Managing Group Policy application and infrastructure Configuring Group Policy settings and preferences Administering network policies Administering remote access Managing file services Monitoring and auditing Windows Server 2012 R2.
Includes index. - Online resource; title from PDF title page (EBSCO, viewed February 5, 2018)
Keywords: Microsoft Windows server; Client/server computing; Architecture client-serveur (Informatique); COMPUTERS; Operating Systems; Windows Server